El Sacramentari de Sant Feliu de Girona (Girona, Museu Diocesà, ms. 46) - Sureda i Jubany, Marc (Miscel·lània litúrgica catalana, 2009)
Despite of its fragmentary state, the Sacramentary of the Collegiate Church of St. Feliu of Girona is probably the most important preserved altar book for the study of the liturgy of the city in its context both local and chronological. Several indices leads to the belief that it could be originated not in the collegiate church, but in the cathedral of St Mary. In any case, the extraordinary manuscript is a witness of the liturgy in Girona specially in the period between 12th-13th centuries, and it includes as well several additions dated until the late 15th.